Impact of high standard farmland construction policy on chemical fertilizer reduction: a case study of China - Yang Liu; Wenmei Liao; Wenmei Liao; Xu Zhang; Hailan Qiu; Hailan Qiu (Frontiers in Environmental Science, 2023)
Promoting chemical fertilizer (CF) reduction is an inevitable requirement for achieving high-quality agricultural development, and high standard farmland construction (HSFC) provides a new path for promoting CF reduction. Takes the implementation of HSFC policy as the starting point, this paper uses the provincial panel data of China from 2005 to 2017 to analyze the impact of HSFC policy on CF reduction and its mechanism of action by using the continuous difference-in-difference (DID) model and mediating model. The baseline regression results show that implementing the HSFC policy has reduced the amount of CF per unit area by 8.9 % on average, which has a significant policy effect. The mechanism analysis shows that the HSFC policy can promote CF reduction by improving the agricultural mechanization level and expanding the scale of operations in agriculture. The results of heterogeneity analysis show that in the natural geographical location dimension, the effect of HSFC policy on CF reduction in the eastern and central regions is more obvious; In the dimension of functional areas of grain production, the impact of HSFC policy on CF reduction in major grain-producing regions is more obvious. Therefore, in the future, it is necessary to continue to vigorously promote the HSFC and give full play to the effective role of HSFC in CF reduction. China should vigorously promote the development level of agricultural mechanization and the large-scale operation of agriculture and further strengthen the HSFC in the western region and non-major grain-producing areas.